The Effect of Emotional and Cultural Intelligences on Networks' Behaviors in International SMEs: Evidence from Portugal - Cabral, Ângelo Miguel R. (2020)
The major purpose of this research was to study the predictive value of the top managers' psychological characteristics regarding their networking behavior. In the international business management context of small- and medium-sized enterprises, we took the top managers' cultural intelligence and emotional intelligence as determinant capabilities to perform better in their external networking. The sample was composed of 307 Portuguese SMEs' international decision-makers, specifically founders, owners, chief executive officers (CEOs), managers of international activities, international market managers, or commercial managers. The data was collected from 2-30 April 2019 through online surveys directed to the Portuguese decision-makers that were directly responsible for the firms' international activities. As a data collection instrument, the surveys were pretested and sent by e-mail. The average age of the participants was approximately 50 years old for males and 45 years old for females. We used self-reported measures to assess the different constructs and the hierarchical regression analysis to test our hypotheses. The results showed that cultural intelligence and emotional intelligence were significant drivers of decision-makers' external networking behavior. A new factor structure concerning external networking behavior was retained. The major results exhibited the predictive value of some cultural and emotional intelligence dimensions over the new retained external networking behavior factors. Therefore, in the international business management context, the capability to adapt to new cultural contexts, as well as the capability to reason about emotions, improved the international decision-makers' external networking behavior.